2003
DOI: 10.1097/01.olq.0000079521.04451.10
|View full text |Cite
|
Sign up to set email alerts
|

Provision of Syndromic Treatment of Sexually Transmitted Infections by Community Pharmacists: A Potentially Underutilized HIV Prevention Strategy

Abstract: Pharmacists are frequently called upon to provide STI treatment but have limited knowledge of correct treatment recommendations. Training pharmacists to provide syndromic STI treatment may be one strategy to reduce STI morbidity and HIV transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 3 publications
0
24
0
Order By: Relevance
“…28 A wide variety of scenarios (n ¼ 64) were covered. This included abortifacients and/or misoprostol requests, 21 34 hypertension, 28 influenza remedies in hypertension, 43 malaria chemoprophylaxis, 41 metronidazole use in pregnancy, 43 migraine, 40 oral and/or emergency contraceptives, 20,23 sexually transmitted infections, 22,29,33,35,38,42,45 steroid requests, 32 and supplying dipyrone or misoprostol without prescription. 43 Several methods were used to conduct these 28 studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…28 A wide variety of scenarios (n ¼ 64) were covered. This included abortifacients and/or misoprostol requests, 21 34 hypertension, 28 influenza remedies in hypertension, 43 malaria chemoprophylaxis, 41 metronidazole use in pregnancy, 43 migraine, 40 oral and/or emergency contraceptives, 20,23 sexually transmitted infections, 22,29,33,35,38,42,45 steroid requests, 32 and supplying dipyrone or misoprostol without prescription. 43 Several methods were used to conduct these 28 studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Eleven studies were conducted in Asian regions: India, 44 Indonesia, 37 Pakistan, 26,27 Thailand, 19,39,40 Turkey, 18 and Vietnam. 22,24,32 Six studies came from African regions: Gambia, 33 Kenya, 29 South Africa, 41,45 Sudan, 36 and Zimbabwe, 35 Lastly, 11 studies were undertaken in Latin American and Caribbean regions: Bolivia, 25 Brazil, 34,38 Colombia, 43 Mexico, 20,21,31,42 Jamaica, 23 Latin American, 30 and both Guatemala and Mexico. 28 A wide variety of scenarios (n ¼ 64) were covered.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have already suggested that pharmacists play a role in preventing the transmission of HIV (Ward et al 2003:609;Watson, Bond & Gault 2003:16). In South Africa, Ward et al (2003) …”
Section: Predisposing Factorsmentioning
confidence: 99%
“…Internationally, there is wide acknowledgement of the underutilization of the pharmacy workforce for public health roles. [5][6][7][8] The provision of pharmacy services in each country revolves around two workforce needs: (1) an appropriately trained pharmacy workforce to provide services, and (2) a competent and committed academic workforce to train sufficient numbers of new pharmacists and other pharmacy support personnel. These in turn depend on suitably resourced academic institutions composed of sufficient numbers of students who have the necessary intellectual and emotional competence to practice.…”
Section: Introductionmentioning
confidence: 99%